SINKRONISASI SWITCHING DAN PENGATURAN DUTY CYCLE PADA DUA INVERTER MOTOR BLDC DENGAN SUMBER TEGANGAN JAMAK - Afiyah Mahirah Rahman; Waru Djuriatno; Muhammad Aswin (Jurnal Mahasiswa TEUB, 2023)
Current technological developments continue to increase in various fields, especially in the field of transportation. The emergence of electric vehicles is the most highlighted today. Electric vehicles are vehicles sourced from electric power that are supplied into the main system as motor drives, one of which is the BLDC Motor. One of the most important things on this system is the voltage source. One of the widely used and developed voltage sources is lithium-ion batteries. However, the use of a single voltage source has several disadvantages, one of which is charging the battery too long, causing too frequent charging and resulting in reduced capability on the battery. The use of multiple voltage sources was chosen in order to reduce the intensity of charging too often. To regulate the use of both voltage sources alternately when the motor is working, two inverters are used to regulate the change of the voltage source. Control of both inverters is regulated by the commutation logic of both inverters and control through the duty cycle on each inverter with different values in the range of State of Charge values of the predetermined battery 1. This research was conducted by simulation using Simulink software which is useful for running simulations in real time and knowing the success of changing voltage sources in the system. Based on simulations, the replacement of the voltage source can be done under the condition that the system is still working and the two inverters are able to work alternately. The test was conducted when battery SoC 1 was at a value of 50% with a duty cycle value of 0.6 for each system. Kata Kunci — Motor BLDC, Sumber Tegangan Jamak, Half Bridge Inverter 3 Fasa, Penggunaan Dua Inverter.